Sintesis hijau dan karakterisasi senyawa basa schiff dari vanilin dan anilina menggunakan metode penggerusan - Maisaroh, Wahdaniati (Maliki Interdisciplinary Journal, 2024)
In general, Schiff bases are organic compounds which are the product of the condensation of aldehydes or ketones with primary amines. Schiff base compounds have many benefits for life, including as a cosmetic or food additive to ward off or block free radicals for the human body. This practicum aims to determine the yield obtained, to determine the melting point of the synthesis product, to determine the solubility of the synthesis product in NaOH solution, and to determine the results of the characterization of the synthesis product. Synthesis products were identified using FTIR, KG-SM, and 1H-NMR spectrophotometers. Schiff basic compound 2-methoxy-4 ((phenilino)methyl)phenol can be synthesized with vanillin and aniline which is carried out by grinding which can cause energy transfer when there is friction and also reduce the formation of by-products that are harmful to the environment and humans themselves. In this research, physical characterization was carried out, including melting point and solubility in NaOH. The characterization results obtained by FTIR obtained a typical absorption of imine functional groups at a wavelength of 1585 cm-1, GC-MS characterization yielded a m/z value of 227 and a base peak of m/z 225 with an area of 98.91%, 1H-NMR characterization obtained imine group at 8.64 ppm. From the data obtained from FTIR, GC-MS, 1H-NMR, it was found that the product of synthesis with a grinding time of 1.37 minutes was a Schiff base compound 2-methoxy-4-( (phenilimino)methyl)phenol with a yield of 81.09%.